2019
DOI: 10.11157/anzswj-vol31iss4id667
|View full text |Cite
|
Sign up to set email alerts
|

A Treaty-based framework for mainstream social work education in Aotearoa New Zealand: Educators talk about their practice

Abstract: INTRODUCTION: Globally, indigenous social work educators have pursued decolonisation and the development of decolonising practices as part of the indigenous peoples’ rights movement and based on social work principles of self-determination and social justice. Māori have advanced decolonisation based on the original partnership that was envisaged in the Treaty of Waitangi signed between Māori and the British Crown in 1840. Aotearoa New Zealand social work education has a stated commitment to a Treaty-based part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…According to Walker (2012), often social worker graduates may not know how to take their knowledge of te Tiriti and embed a bicultural approach in practice. Educators can be tasked to teach about biculturalism and other concepts they do not have sufficient knowledge of or are comfortable to teach (Hetaraka, 2019;McNabb, 2019). We suggest that social workers may also be ill equipped to also connect this knowledge with diversity.…”
Section: Education and The Fundamentals Of Social Workmentioning
confidence: 97%
See 2 more Smart Citations
“…According to Walker (2012), often social worker graduates may not know how to take their knowledge of te Tiriti and embed a bicultural approach in practice. Educators can be tasked to teach about biculturalism and other concepts they do not have sufficient knowledge of or are comfortable to teach (Hetaraka, 2019;McNabb, 2019). We suggest that social workers may also be ill equipped to also connect this knowledge with diversity.…”
Section: Education and The Fundamentals Of Social Workmentioning
confidence: 97%
“…These social workers identified that the knowledge of te Tiriti gained in their education did support them in their engagement with diversity on an interpersonal level; however, they could not seem to connect this with understandings or practice with diversity (McNabb, 2019;Walker, 2012). According to Walker (2012), often social worker graduates may not know how to take their knowledge of te Tiriti and embed a bicultural approach in practice.…”
Section: Education and The Fundamentals Of Social Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Coinciding with Awatere's life trajectory, structural and radical social work was predominantly developed through the 1960s to 1980s, with feminist social work models focusing particularly on stepping away from individualised responses to politicise personal experiences (Fook, 2016). Awatere's (1984) perceptive assertion that there is a need to "shift out of the 'tripod' framework of racism, sexism and capitalism" (p. 8) is congruent with contemporary social work teaching about the need to critically appreciate the intersectional identities of individuals, families, groups and communities to discern the power of socio-political forces impacting upon them (Crenshaw, 1991;Joy, 2019;McNabb, 2019;Social Workers Registration Board, 2023a). The social work profession is often funded by the state and can be a tool of the state to exercise social control over oppressed populations, specifically Māori as Tangata Whenua (Indigenous people).…”
Section: Positioning Social Work Educationmentioning
confidence: 99%
“…For social work educators, the complexity of abiding by the profession's commitment to Te Tiriti o Waitangi has been proven to be difficult, due in part, to the dynamic manner in which society reacts to Te Tiriti over time (McNabb, 2019). Social work is currently on the New Zealand Immigration (2023) Green List due to workforce shortages, being on the Green List enables employers to guarantee residence pathways for hard-tofill occupations.…”
Section: Accomplices Separate But Togethermentioning
confidence: 99%